Japanese national survey on declined liver allografts from brain‐dead donors: High decline rate but promising outcomes in allografts with moderate steatosis - Yusuke Takemura; Masahiro Shinoda; Yasushi Hasegawa; Yohei Yamada; Hideaki Obara; Minoru Kitago; Mureo Kasahara; Koji Umeshita; Susumu Eguchi; Yuko Kitagawa; Hideki Ohdan; Hiroto Egawa (Annals of Gastroenterological Surgery, 2023)
Abstract Aim Liver allografts from brain‐dead donors, which were declined and were eventually not transplanted due to accompanying marginal factors, have never been surveyed in Japan. We surveyed the declined allografts and discussed the graft potential focusing on various marginal factors. Methods We collected data on brain‐dead donors between 1999 and 2019 from the Japan Organ Transplant Network. We divided their liver allografts into declined (nontransplanted) and transplanted ones, and then characterized declined ones focusing on their timepoints of decline and accompanying marginal factors. For each marginal factor, we calculated the decline rate from the number of declined and transplanted allografts, and assessed the 1‐year graft survival rate from transplanted allografts. Results A total of 571 liver allografts were divided into 84 (14.7%) declined and 487 (85.3%) transplanted ones. In the declined allografts, a majority was declined after laparotomy (n = 55, 65.5%), most of which had steatosis and/or fibrosis (n = 52). Out of the moderate steatotic (without F ≥ 2 fibrosis) allografts (n = 33), 21 were declined and 12 were transplanted, leading to a 63.6% decline rate. The latter 12 achieved a 92.9% 1‐year graft survival rate after transplantation. Comparison of donor background showed no significant difference between the declined and transplanted allografts. Conclusion Pathological abnormalities of steatosis/fibrosis seem to be the most common donor factor leading to graft decline in Japan. Allografts with moderate steatosis were highly declined; however, transplanted ones achieved promising outcomes. This national survey highlights the potential utility of liver allografts with moderate steatosis.